2022
DOI: 10.1101/2022.10.27.514070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-nucleus and spatial transcriptomic atlas of the COVID-19 liver reveals topological, functional, and regenerative organ disruption in patients

Abstract: The molecular underpinnings of organ dysfunction in acute COVID-19 and its potential long-term sequelae are under intense investigation. To shed light on these in the context of liver function, we performed single-nucleus RNA-seq and spatial transcriptomic profiling of livers from 17 COVID-19 decedents. We identified hepatocytes positive for SARS-CoV-2 RNA with an expression phenotype resembling infected lung epithelial cells. Integrated analysis and comparisons with healthy controls revealed extensive changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…Reads were aligned against the GRCm38 mouse genome assembly and gene counts were obtained, per-droplet, by summarizing exonic and intronic UMIs that overlapped with the GENCODE mouse annotation (release 24) for each gene symbol. In order to adjust for downstream effects of ambient RNA expression within mouse nuclei, we used the ‘remove-background’ module from CellBender ( Pita Juarez et al, 2022 ; version 0.2.0) to remove counts due to ambient RNA molecules from the count matrices and to estimate the true cells. Genes were subsequently filtered such that only genes detected in two or more cells and with at least 6 total counts (across all cells) were retained.…”
Section: Methodsmentioning
confidence: 99%
“…Reads were aligned against the GRCm38 mouse genome assembly and gene counts were obtained, per-droplet, by summarizing exonic and intronic UMIs that overlapped with the GENCODE mouse annotation (release 24) for each gene symbol. In order to adjust for downstream effects of ambient RNA expression within mouse nuclei, we used the ‘remove-background’ module from CellBender ( Pita Juarez et al, 2022 ; version 0.2.0) to remove counts due to ambient RNA molecules from the count matrices and to estimate the true cells. Genes were subsequently filtered such that only genes detected in two or more cells and with at least 6 total counts (across all cells) were retained.…”
Section: Methodsmentioning
confidence: 99%
“…Pita-Juarez et al leveraged the GeoMx DSP Whole Transcriptome Atlas platform to spatially analyze human livers from patients with coronavirus disease 2019 (COVID-19) infection and found that COVID-19-specific liver modulation was observed, such as hepatocyte proliferation in zone 1 and hypoxia and stress response in zone 3. 85 Uzun et al compared liver injury after COVID-19 vaccination (vaccine-induced liver injury [VILI]) with autoimmune hepatitis (AIH), since their clinical presentation to some extent resembles each other, using DSP in conjunction with bulk RNA-sequencing. 86 Bulk RNA-sequencing revealed that interferon gamma pathways were significantly enriched in AIH, whereas mitochondrial metabolism and oxidative stress-related pathways were upregulated in VILI, and DSP suggested that hepatocytes were responsible for these differences.…”
Section: Acute Liver Injury and Regenerationmentioning
confidence: 99%
“…7 B). Comprehensive single-cell/spatial organ atlases of COVID-19 have been generated from various types of patient samples, including livers, using available scRNA-seq and spatial data [ 166 169 ]. By performing scRNA-seq and spatial transcriptomic profiling of livers from 17 COVID-19 patients, hepatocytes were identified as positive for SARS-CoV-2 RNA [ 169 ].…”
Section: Spatial and Single-cell Transcriptomics In The Liver During ...mentioning
confidence: 99%
“…Comprehensive single-cell/spatial organ atlases of COVID-19 have been generated from various types of patient samples, including livers, using available scRNA-seq and spatial data [ 166 169 ]. By performing scRNA-seq and spatial transcriptomic profiling of livers from 17 COVID-19 patients, hepatocytes were identified as positive for SARS-CoV-2 RNA [ 169 ]. Further integrated analysis and comparisons with healthy controls revealed massive changes in cellular composition and gene expression in livers affected by COVID-19, mainly in those exhibiting hepatocellular injury, ductular reactions, pathologic vascular expansion, and fibrogenesis (Fig.…”
Section: Spatial and Single-cell Transcriptomics In The Liver During ...mentioning
confidence: 99%
See 1 more Smart Citation